First love simplicity: A systemic-functional perspective study of Karina Del Campo’s Do You Remember Our Love? - Sugeng Purwanto; Idha Nurhamidah (EduLite: Journal of English Education, Literature and Culture, 2018)
The current study aims at exploring the intended meaning and structure of a poem entitled ‘Do You Remember Our Love?’ written by a poet, © Karina Del Campo (2009) in both interpretational and systemic functional perspectives. In the former, the poem was examined interpretatively in order to find out the possible stance of the poet; meanwhile the later was an analytical representation of systemic functional grammar in the framework of construing the three domains of meanings: ideational, interpersonal and textual in order to arrive at the field, the tenor and the mode of the discourse.  It turns out that the poem is  a reflection of a woman’s feeling (the poet’s) toward her ex-boyfriend—finely described in a repeated style of the major clause, supported and elaborated in several minor clauses. The poet tries very hard to ignite her ex-boyfriend’s love memories with her and to possibly invite him to reunite even though it seems to be a mission impossible. The poem has both social and psychological impacts on the poet herself and the readers in a wider scope.